Effect of Defoliation on Growth and Yield of Maize (Bangladesh Agronomy Journal, 2023)
The experiment was conducted to evaluate the effect of defoliation on grain and fodder yield of maize at the research field and laboratory of Crop Physiology and Ecology Department, Hajee Mohammad Danesh Science and Technology University, Dinajpur during the period of December 2018 to June 2019. The trial was carried out in a randomized completely block design with three replications. The experimental treatments were: T1– Control (without leaf removal), T2–Defoliating all leaves except ear and adjacent two leaves above the ear at 7 days after silking (DAS), T3–Defoliating all leaves except ear and adjacent two leaves above the ear at 14DAS, T4–Defoliating all leaves below the ear at 7 DAS, T5–Defoliating all leaves below the ear at 14 DAS, T6– Detopping except two leaves above the ear at 7 DAS and T7–Detopping except two leaves above the ear at 14 DAS. Light intensity was increased (66.9 to 81.05%) when only lower leaves (T5) or both upper and lower leaves (T2) were removed, but when only the upper leaves (T6) were removed it was not increased. SPAD value was increased (13.58 to 24.5%) but number of leaves and leaf area plant-1 were reduced (60.5 to 63.09% and 64.4%) due to defoliation. Substantial amount of green fodder was obtained (0.776 Kg m-2) due to defoliation of maize. Grain yield of maize was reduced (5.56 to 21.83%) due to different defoliation treatments but the yield reduction was not significant when only lower (T4) or upper (T7) leaves were removed.Bangladesh Agron. J. 2022, 25(2): 31-41